Three fat virgins unassembled - Zahim Albakri,; Leow, Puay Tin *; Yu, Ovidia; Tey, Cindy *; Foo, Helena *; Teh, Joylynn *; Nurul Ain Mohammed Jamlus, (Sunway University. Dept. of Performance & Media, 2006)
Singaporean playwright Ovidia Yu's much-loved satire centres on a group of women trying to free themselves from the "fat virgin" syndrome, that is, society's expectations of them as career woman, daughter, girlfriend, wife and mother. Quirky and witty, the play sets out to question the way women think of themselves and the roles that others perceive them in. References including names and places have been changed to keep the text relevant and to help audiences better understand the sometimes dark humour of the play.